“The unexamined life is not worth living”: philosophy in the intertwinement of life and knowledge (Nóema, 2017)
The essay compares the Socratic idea of an infinite inquiry, considered as the moving inspiration of philosophy (and hereby defined as ‘zetetics’) and the idea, analyzed in contemporary epoch especially by Peirce and Wittgenstein, of a knowledge based on the pure description of life and its pragmatic forms, of the indubitable certainty that is the ground of any evidence, acquired through a rigorous zetetics. Here the inquiry is: how can we configure the philosophical method – meth’odos, path – in the intertwinement between lived life and examined life?
Keywords: zetetics; ethics; pragmatics; Socrates; Peirce; Wittgenstein